2004
DOI: 10.1124/jpet.104.074898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Antimuscarinic Action of p-Fluorohexahydrosiladifenidol in Ileal and Tracheal Smooth Muscle

Abstract: We investigated the ability of the muscarinic antagonist pfluorohexahydrosiladifenidol to inhibit muscarinic agonist-induced contractions and phosphoinositide hydrolysis in the guinea pig ileum and trachea. This antagonist displayed higher potency at blocking oxotremorine-M-induced contractions of the ileum compared with those of the trachea. When estimated using a simple model for competitive antagonism, the observed dissociation constant of p-fluorohexahydrosiladifenidol exhibited approximately 12-fold highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…For example, the compound zamifenacin inhibits muscarinic agonist-induced contraction of the guinea-pig ileum, trachea, and urinary bladder with high (pK B ¼ 9.3), intermediate (pK B ¼ 8.2), and low potency (pK B ¼ 7.6), respectively (Wallis 1995;Watson et al 1995), and the compound p-F-HHSiD exhibits a similar pattern of selectivity with regard to ileum and trachea (Eglen et al 1990;Ehlert et al 2005b). These compounds exhibit high affinity for M 3 , low affinity for M 2 , and variable affinity for the other muscarinic subtypes when measured in radioligand binding assays on Chinese hamster ovary (CHO) cells stably expressing human muscarinic receptor subtypes.…”
Section: Tissue-selective Muscarinic Antagonists?mentioning
confidence: 87%
See 3 more Smart Citations
“…For example, the compound zamifenacin inhibits muscarinic agonist-induced contraction of the guinea-pig ileum, trachea, and urinary bladder with high (pK B ¼ 9.3), intermediate (pK B ¼ 8.2), and low potency (pK B ¼ 7.6), respectively (Wallis 1995;Watson et al 1995), and the compound p-F-HHSiD exhibits a similar pattern of selectivity with regard to ileum and trachea (Eglen et al 1990;Ehlert et al 2005b). These compounds exhibit high affinity for M 3 , low affinity for M 2 , and variable affinity for the other muscarinic subtypes when measured in radioligand binding assays on Chinese hamster ovary (CHO) cells stably expressing human muscarinic receptor subtypes.…”
Section: Tissue-selective Muscarinic Antagonists?mentioning
confidence: 87%
“…This technique enables one to estimate the pK B of the competitive component based on the ability of the antagonist to interfere with the competitive effect of a purely competitive antagonist, like atropine, for example. When this approach was used on guinea-pig ileum and trachea to measure the competitive component of the inhibitory effect of p-F-HHSiD on muscarinic agonist-induced contraction, it was found that p-F-HHSiD exhibited similar pK B values for inhibition of agonist-induced contraction of ileum and trachea (Ehlert et al 2005b). Thus, there is no reason to suggest that p-F-HHSiD competitively antagonizes muscarinic responses with different affinities in different tissues.…”
Section: Tissue-selective Muscarinic Antagonists?mentioning
confidence: 96%
See 2 more Smart Citations
“…Male albino guinea pigs with 300–450 g body weight were used. They were fasted for 24 h and fed with water as required 14,15 . The animals were euthanized by stunning, incision into the carotid and exsanguination.…”
Section: Methodsmentioning
confidence: 99%